Influence of Nb, Ta and Zr on the Interdiffusion Coefficients and Solid Solution Strengthening of γ-TiAl Single Phase Alloys - Haußmann, Lukas; Neumeier, Steffen; Bresler, Johannes; Keim, Simon; Pyczak, Florian; Göken, Mathias (Metals, 2022)
The alloying elements Nb, Ta and Zr improve the creep properties of fully lamellar γ/α2 titanium aluminides significantly. Since high temperature deformation mainly occurs in the γ-phase of γ/α2 titanium aluminides, the diffusivity and the solid solution hardening effect of these three elements in the γ-phase is studied by analyzing the concentration gradients of the alloying elements and the resulting hardness across the interdiffusion zone of diffusion couples by energy dispersive X-ray diffraction and nanoindentation. The results reveal that Zr has the highest interdiffusion coefficient but also the largest solid solution hardening coefficient. The mechanical properties of single γ-phase Ti-54Al-5X alloys were investigated by strain rate jump tests. The addition of 5 at.% Nb or Ta lead to an increased strength compared to a binary γ-Ti-54Al alloy. The Zr-containing γ-TiAl alloy reveals the highest strength at 750°C and 900°C, which is discussed to be due to the strong solid solution hardening effect of Zr. However, in comparison to the other alloys, Ti-54Al-5Zr shows quite brittle behavior up to 900°C. The lower diffusivity of Ta compared to Nb leads to a higher strength of the Ta-modified alloy at 900◦C.
CRIS-Team Scopus Importer:2022-05-13
Keywords: diffusion; solid solution hardening; strain rate jump test; TiAl; γ-phase